Lack of Association Between TNF-α, IFN-γ, IL-10 Gene Polymorphisms and Rheumatic Heart Disease in South Indian Population. (3rd September 2018) - Poomarimuthu, Maheshkumar; Elango, Sivakumar; Solomon, Pravin Raj; Soundarapandian, Sambath; Mariakuttikan, Jayalakshmi
Abstract: Background: Proinflammatory and anti-inflammatory cytokines play a crucial role in the development and maintenance of immune mediated inflammatory diseases including rheumatic heart disease (RHD). Polymorphisms in tumor necrosis factor ( TNF ) - α, interferon ( IFN ) -γ, and interleukin ( IL )-10 genes influence the differential cytokine expression as well as the pathogenesis of various inflammatory and autoimmune diseases. Objective: The aim of the study is to investigate the association between TNF-α, IFN-γ, and IL-10 gene polymorphisms and RHD in South Indian population. Materials and Methods: TNF-α (–308, –238), IFN-γ (+874), and IL-10 (–1082, –819, –592) gene polymorphisms were determined in 100 patients with RHD and 127 healthy siblings by PCR. Results: There was no significant difference in the genotype, allele, and haplotype frequencies of TNF-α, IFN-γ, and IL-10 polymorphisms between RHD patients and healthy siblings. Conclusion: The present study suggests that TNF-α, IFN-γ, and IL-10 gene variants may not be associated with the development of RHD in South Indian population.